2017
DOI: 10.1620/tjem.242.259
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Support Team for Frail, Disabled, or Elderly People during the Early Phase of a Disaster

Abstract: Japan was struck by two catastrophic disasters on March 11, 2011 and on April 16, 2016. The former was the Great East Japan Earthquake (M9.0) and the latter was the Kumamoto Earthquake (M7.0). Most inhabitants in the affected areas of both disasters were forced to live in evacuation centers right after the earthquake. Poor oral hygiene, inactivity, malnourishment, appetite loss, eating problems, and swallowing problems due to lack of support for frail, disabled, or elderly evacuees occur during the early phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“… 21 Another study reported that too many people were evacuated to the shelters in Kumamoto prefecture and the cramped accommodations left little room to walk between beds. 22 Some of the evacuees in these shelters tried not to move into the shelters. 22 The density of evacuees in shelters may have led to outbreaks of vaccine-preventable ACSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 Another study reported that too many people were evacuated to the shelters in Kumamoto prefecture and the cramped accommodations left little room to walk between beds. 22 Some of the evacuees in these shelters tried not to move into the shelters. 22 The density of evacuees in shelters may have led to outbreaks of vaccine-preventable ACSCs.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Some of the evacuees in these shelters tried not to move into the shelters. 22 The density of evacuees in shelters may have led to outbreaks of vaccine-preventable ACSCs. Early intervention can prevent progression of acute ACSCs to more serious conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Disaster rehabilitation (2) and feeding support teams (19) worldwide should better organize efforts to address the large population of elderly survivors with special food intake needs, including those at risk of aspiration solely when consuming regularly distributed emergency foods. Studies have reported the effects of disaster rehabilitation on improvements in physical function, post-traumatic stress disorder, quality of life, and re-employment among disaster victims with various disorders (20).…”
Section: Discussionmentioning
confidence: 99%
“…We also recommend maintenance of activity levels (avoiding hospital‐associated deconditioning) in such patients with poor cough sensitivity, in addition to several drugs, oral care and oral intake. A decline in physical activity might increase the potential risk for decline of expiratory and swallowing muscle strength, resulting in failure to recover from the pneumonia and relapse of the aspiration pneumonia …”
Section: Discussionmentioning
confidence: 99%
“…A decline in physical activity might increase the potential risk for decline of expiratory and swallowing muscle strength, resulting in failure to recover from the pneumonia 9 and relapse of the aspiration pneumonia. 23 There were some limitations to the study. We excluded patients with consciousness issues.…”
Section: Discussionmentioning
confidence: 99%